Railway Heritage of the Samaritá station in São Vicente - SP - Romão, Kauê Marques; Fiorin, Evandro (National Journal of City Management, 2022)
During the economic cycle of coffee and technological development attributed to the arrival of railways on the coast of São Paulo, São Vicente – SP as well as the cities of the interior of the state of São Paulo, witnessed potential economic and urban advances generated by industrial activities throughout the first half of the twentieth century. From the implementation of the railway, eight railway stations were built in the mountains and on the continental plain of the city being, the first, Samaritá. Given this importance, we justify this research in order to build an understanding about the apogee and decay of railway and industrial heritage in the city, under the section of this station. Based on historiographical research through maps, photographs and documents it was possible to clearly understand the implementation of the railway bed in the continental region of the city, where new urban groupings derived from the railway tracks had emerged. The vast majority of São Vicente's railway stations have been abandoned or demolished, and the last exemplary on the Vicentine plain that remains is samaritá station. Thus, the work analyzes either the emergence of the railroad, from the perspective of the building that generates the first occupation in the continental plain of the city and its process of deterioration, when presenting the current situation of the railway complex.